Environmental wellbeing in the context of sustainable development: Evidence from post-communist economies - Ulman, Simona-Roxana; Mihai, Costica; Cautisanu, Cristina; Brumă, Ioan-Sebastian; Coca, Oana; Stefan, Gavril (Frontiers in Environmental Science, 2022)
Considering the diverse national contexts, there are certainly differences with regard to their capacity of attaining sustainability and its three main dimensions. The present study puts face to face the economic, social, and environmental indicators from 19 post-communist economies across the 2006–2020 period; emphasizes the main vulnerabilities that are commune at the level of the analysed countries; concentrates on these weak points; and intends to offer concrete explanations regarding the main social and economic factors exerting a negative influence on them. Consequently, placing Climate & Energy, with their major components, i.e., energy use, energy savings, greenhouse gases, and renewable energy, in the centre of the analysis, as the major weak points of environmental wellbeing within the analysed group of countries, the nature of the influence of human and economic wellbeing upon each of them was evidenced using panel data-specific methods (pooled, fixed, and random effects). The general results obtained showed that: (1) the components of the Environmental Wellbeing registered a different evolution among the post-communist economies; (2) Climate & Energy components were the main vulnerabilities in terms of environmental sustainability; (3) these environmental components were closely linked to both components of economic and social dimensions, and (4) the determinants of energy use, energy savings, greenhouse gases and renewable energy were different in the selected group of countries. This study draws the attention on the fact that the patterns of development applied in the group of post-communist economies seem to strengthen the sustainable goals especially in regard to economic and human wellbeing. Moreover, while directing its focus on main urgent environmental vulnerabilities and encouraging their strengthening through the option of not putting the economic dimension in the centre of interest, it constitutes into a piece of support for the theoretical perspective of sustainable wellbeing, based on the background of sustainability and ecological economics.